Pharmacokinetic data in pregnancy: A review of available literature data and important considerations in collecting clinical data - Coppola, Paola; Kerwash, Essam; Nooney, Janet; Omran, Amro; Cole, Susan (Frontiers in Medicine, 2022)
Pregnancy-related physiological changes can alter the absorption, distribution, metabolism and excretion of medicines which may affect the safety and efficacy of the medicines administered in pregnancy. Pharmacokinetic data can thus be instrumental in supporting dose adjustments required in this population. This review considers the availability of published pharmacokinetic data for over 200 medicines of interest for use in pregnancy in the UK, to identify whether sufficient data currently exists, in principle, for any medicine or group of medicines to support dose adjustments to maintain maternal health through pregnancy. Very limited data was found for many of the medicines of interest. Nevertheless, well documented, large changes of exposure for some drugs, where data is available, highlights the urgent need to collect more data of good quality to inform appropriate doses, when needed, in this population. In addition, clinical study methodology can have an impact on the usefulness of the data and key clinical design aspects are highlighted for consideration in future clinical study design.